Expression Analysis of COPB2 and Bcl-2 in Early Stages of Endometrial Carcinoma - Branko Andrić; Danijela Cvetković; Stefan Blagojević; Marko Stanković; Nenad Kokošar; Dragutin Sretenović; Dragiša Šljivančanin; Branislav Milošević; Danijela Milošev; Petar Arsenijević (IMR Press, 2023)
Background: Coatomer protein complex subunit β2 (COPB2) is a subunit of the intracellular transport system between cell organelles that participates in the regulation of cell division and differentiation. Bcl-2 is a protein that participates in regulating the process of apoptosis. We aimed to examine and establish expression of these two genes in endometrial cancer at an early stage. Methods: In order to examine the relative expression of the gene for the COPB2 subunit and Bcl-2, we sampled endometrial tissue from 40 patients with endometrial cancer (experimental group) and from 20 patients without cancer (control group). All patients in the experimental group had early-stage cancer without metastases at the time of sample collection. Gene expression was performed using the polymerase chain reaction (PCR) method at the Faculty of Science, University of Kragujevac. Relative quantification of COPB2 and Bcl-2 gene expression was obtained in relation to the expression of GAPDH ("housekeeping gene"). Based on the results of the analysis of the normality of the data distribution (Shapiro-Wilk test), the Mann-Whitney U test was used for the analysis of these variables. Results: Using Mann-Whitney U test, we determined that there is a statistically significant difference (p < 0.05) in the expression values of the COPB2 and Bcl-2 gene in women with endometrial carcinoma (EC) compared to women without cancer. Expression value for the COPB2 gene in the experimental group (0.18) was lower compared to the value of the control group (0.65). Also, the relative expression value of Bcl-2 was lower in the examined group (0.15) than in the control group (0.54). Receiver operating characteristic (ROC) curve showed statistically significant diagnostic potential of gene expression for COPB2 (area under the curve (AUC) 0.878; p < 0.001) and Bcl-2 (AUC 0.666; p = 0.038). Conclusions: In the initial stages of endometrial cancer, there is a significant reduced expression of the Bcl-2 and COPB2 gene compared to cells of normal endometrial tissue. This study showed that the expression value of these two genes in the early stages of endometrial cancer is low. Diagnostic potential in segregation of cancer from non- cancer patients is achieved through expression of these two genes, with COPB2 being more specific biomarker. Clinical Trial Registration: The study has been registered with registration number NCT05951426 on https://classic.clinicaltrials.gov/ct2/home.